Clinical evaluation of cefotiam in the treatment of bacteremia caused by Escherichia coli, Klebsiella species, and Proteus mirabilis: A retrospective study. Issue 11 (November 2020) - Hashiguchi, Yumi; Oda, Kazutaka; Katanoda, Tomomi; Nosaka, Kisato; Jono, Hirofumi; Saito, Hideyuki
Abstract: Bacteremia is often caused by gram-negative bacteria (represented by EKP; Escherichia coli, Klebsiella species, and Proteus mirabilis ), and the excessive use of cefazolin, as the first-line antimicrobial in its treatment, has been a source of concern in the emergence of resistant strains. As an antimicrobial, cefotiam may be an alternative to cefazolin; however, little evidence is available for its use in the treatment of bacteremia. The purpose of this non-inferiority study was to retrospectively compare the therapeutic efficacy of cefotiam with some antimicrobials of narrow spectrum (cefazolin, cefmetazole, and flomoxef) in the treatment of EKP-induced bacteremia. The number of patients recruited was 32 in the cefotiam group and 29 in the control group. In the primary endpoint, the survival rate on day 28 for the cefotiam group and the control group was 93.5% and 89.3%, respectively (relative risk at day 28, 1.048; 95% confidence interval, 0.894–1.227). In the secondary end point, treatment success rate in the two groups was 71.9% and 69.0%, respectively (relative risk, 1.042; 95% confidence interval, 0.752–1.445). Intensive care unit admission, low body weight, hypoalbuminemia, and infections unassociated with the urinary tract were identified to be the risk factors responsible for treatment failure. We demonstrated cefotiam may be non-inferior to other antimicrobials of similar spectrum, in terms of survival rate, in EKP-induced bacteremia.